EVALUASI PELAKSANAAN PROGRAM LAYANAN ASPIRASI DAN PENGADUAN ONLINE RAKYAT (LAPOR!) DALAM MEWUJUDKAN GOOD GOVERNANCE (Studi Kasus Kantor Staf Presiden Republik Indonesia) - Yulistiono YS, Moh. Dedy Pratama; Yasintha, Putu Nomy; Winaya, I Ketut (CITIZEN CHARTER, 2018)
ABSTRACT LAPOR! can be said to be successful as the national-based complaint system not only seen from its objective to increase community participation that has been achieved but also from the development of program implementation system through evaluation. This research uses the theory of policy evaluation from William N Dunn consisting of evaluation criteria which are adequacy, effectiveness, equity, efficiency, responsiveness, and appropriateness. The theoretical as its implementation has met the criteria of responsiveness, effectiveness, adequacy, and_accuracy can be seen from the purpose of its formation. However, from the indicators of efficiency it is still not maximal due to lack of admin power as a manager of complaints facilities connected to the smallest administrative government. Based_on the principles_of good_governance in term of public complaints system, program of LAPOR! has fulfilled some of indicator for the principles that exist as the public complaint system. Keywords: Evaluation, complaint system, good governance